PRESERVATION THE TRADITIONS OF UKRAINIAN SPIRITUAL CHOIR CULTURE IN MUSIC SCIENTIFIC RESEARCH BY MYRON FEDORIV - Yatsiv I. V. (International Journal of Innovative Technologies in Social Science, 2021)
The article is devoted to the evaluation of scientific works of the well - known in the Ukrainian diaspora musicologist and publicist Myron Fedoriv in the context of the preservation of national song traditions outside the ethnic territory. The information on the most important theoretical achievements of the scientist is given, the place and value of activity of the cultural public figure in the history of musical and choral culture of Ukraine and the western diaspora is defined. The author notes that Myron Fedoriv lived most of his life in the United States. He left a large amount of musical material and theoretical works in the history of Ukrainian choral culture, so he stopped the destruction of song traditions and examples of canonical liturgical singing in Ukrainian churches of the diaspora. In his works, Myron Fedoriv wrote that the singing tradition is the basis of the Ukrainian national spiritual culture, and therefore it should be preserved in the Ukrainian Catholic Church in America. As a result, the musicological heritage of Myron Fedoriv is very valuable for the Ukrainian musical culture of the twentieth century. Thus, its activities deserve more detailed study.